2021
DOI: 10.1002/slct.202100945
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Performance of Copper‐Manganese Composite Oxide Catalysts for Toluene

Abstract: Copper-manganese (CuMn) composite oxide catalysts were prepared for the catalytic combustion of a common volatile organic compound, namely toluene. The structural properties of the catalysts were analysed by X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) theory, X-ray photoelectron spectroscopy (XPS) and hydrogen temperature-programmed reduction (H 2 -TPR). The catalytic stability was examined after 100 h. It was found that Cu 1 Mn 1 exhibited the highest catalytic ability when the molar ratio of Cu : M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The stability of the catalyst toward toluene oxidation is an essential factor. The stability (continuous reaction for 70 h) of Cu 2 Mn 1 , Cu 2 Mn 1 , and Cu 2 Mn 1, prepared at calcination temperature of 500°C are shown in Figure 12 26 . At space velocity 12,000 h −1 , reaction temperature of 260°C, and toluene concentration of 500 mg/m 3 , the catalytic performance of the catalysts did not change and remained stable for a long reaction time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of the catalyst toward toluene oxidation is an essential factor. The stability (continuous reaction for 70 h) of Cu 2 Mn 1 , Cu 2 Mn 1 , and Cu 2 Mn 1, prepared at calcination temperature of 500°C are shown in Figure 12 26 . At space velocity 12,000 h −1 , reaction temperature of 260°C, and toluene concentration of 500 mg/m 3 , the catalytic performance of the catalysts did not change and remained stable for a long reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…The stability (continuous reaction for 70 h) of Cu 2 Mn 1 , Cu 2 Mn 1 , and Cu 2 Mn 1, prepared at calcination temperature of 500 C are shown in Figure 12. 26 At space velocity 12,000 h À1 , reaction temperature of 260 C, and toluene concentration of 500 mg/m 3 , the catalytic performance of the catalysts did not change and remained stable for a long reaction time. Thus, it can be concluded that the Cu 2 Mn 1 catalyst not only has high catalytic performance, but also has good stability, which is suitable for the catalytic reaction of toluene (Figure 13).…”
Section: Catalyst Stability Testmentioning
confidence: 96%
“…Volatile organic compounds (VOCs) with a great toxicity to human health mainly come from the industrial exhaust gas during petrochemical, pharmaceutical, printing and burning processes. [1,2] Formaldehyde (HCHO), one of the representative VOC pollutants, tends to cause neurological dementia, [3] lung injury, [4] myeloid leukemia, [5] and teratogenicity. [6] The efficient detection and elimination of HCHO molecules remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that industrial CVOCs exist in the form of low concentration and high throughput, catalytic oxidation has become one of the most feasible, economical and reliable method due to its high efficiency and selectivity at low temperature. Generally, catalytic oxidation is closely related to catalysts, and finding highly efficient catalysts is the main direction of efforts [6–9] . During the past decades, the catalysts used for catalytic oxidation of CB could be mainly divided into three categories, namely noble metals, metal oxides and perovskite‐type catalysts [10–12] .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, catalytic oxidation is closely related to catalysts, and finding highly efficient catalysts is the main direction of efforts. [6][7][8][9] During the past decades, the catalysts used for catalytic oxidation of CB could be mainly divided into three categories, namely noble metals, metal oxides and perovskite-type catalysts. [10][11][12] However, the noble metal catalysts are expensive and susceptible to chlorine poisoning, and perovskite-type catalysts have poor porosity and undesirable redox properties, resulting in unsatisfactory activity at low temperature, all of which limit their practical application in industry.…”
Section: Introductionmentioning
confidence: 99%